Panasonic Life Solutions : rethinking its approach to employee experience management - Mehrotra, Sonia, (SAGE Business cases., 2024)
The case recounts the organizational strategies of Panasonic Life Solutions India Limited (PLSIND) in the past two decades of its operations in India. PLSIND started its India operations by acquiring a family-managed business. It details Human Resources’ (HR) role as a business enabler across the different phases of the PLSIND growth journey. In particular, it explores the significance of an alignment between the HR function and business functions for successful organizational outcomes. The case encourages students to consider frameworks and concepts on strategic HR management, human capital strategy, and the use of integrated cloud-based human capital management software, provoking thoughts about ideas and new approaches to overall talent management for improved business productivity and profitability.